Five Chapters on Rhetoric : Character, Action, Things, Nothing, and Art - Kochin, Michael Shalom, 1970- (Book collections on Project MUSE., 2009)
"Examines concepts for persuasive communication. Explores the art of rhetoric and how it aids in clarification when we speak to communicate, but also helps to protect us from clarity when we speak to maintain our connections to others"--Provided by publisher.